ANALISIS KEDISIPLINAN MAHASISWA PENJASKESREK FKIP UNRI DALAM PROSES BELAJAR MENGAJAR DARING - Fauji, Aminul; Wijayanti, Ni Putu Nita; Hidayat, Hirja (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: In general, this study aims to determine the Discipline Analysis of Penjaskesrek FKIP UNRI students in the Online Teaching and Learning Process. The population in this study were students of the Riau University's health and recreation physical education study program class 2018, 2019 and 2020. totaling 232 students. The data collection technique uses a questionnaire instrument (questionnaire) via google form. The analysis technique used is to pour the frequency into the form of a percentage. The results of this study indicate that the Discipline Analysis of the Penjaskesrek FKIP UNRI students in the Online Teaching and Learning Process is said to be very good. With consideration based on the results of the research and discussion that has been presented, it can be concluded that the Discipline Analysis of the Penjaskesrek FKIP UNRI students in the Online Teaching and Learning Process is said to be very good. Considering the highest frequency is in the